2016
DOI: 10.1016/j.cmi.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of excess mortality due to carbapenem-resistant Klebsiella pneumoniae infections

Abstract: Patients infected or colonized with carbapenem-resistant Klebsiella pneumoniae (CRKp) are often chronically and acutely ill, which results in substantial mortality unrelated to infection. Therefore, estimating excess mortality due to CRKp infections is challenging. The Consortium on Resistance against Carbapenems in K. pneumoniae (CRACKLE) is a prospective multicenter study. Here, patients in CRACKLE were evaluated at the time of their first CRKp bloodstream infection (BSI), pneumonia, or urinary tract infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 28 publications
2
73
1
4
Order By: Relevance
“…Urinary tract infections were reported to have limited mortality (19)(20)(21). For carbapenem-resistant K. pneumoniae infections, pneumonia and bloodstream infections were related to high mortality risks, while urinary tract infections showed no excess mortality (21). Bacteremia presented a high death rate in this study, with an overall mortality of 43.1%.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Urinary tract infections were reported to have limited mortality (19)(20)(21). For carbapenem-resistant K. pneumoniae infections, pneumonia and bloodstream infections were related to high mortality risks, while urinary tract infections showed no excess mortality (21). Bacteremia presented a high death rate in this study, with an overall mortality of 43.1%.…”
Section: Discussionmentioning
confidence: 55%
“…Carbapenem-resistant K. pneumoniae nonbacteremic infections were associated with 24.3% mortality, and 40% of patients with lower respiratory tract infections eventually died (19). Urinary tract infections were reported to have limited mortality (19)(20)(21). For carbapenem-resistant K. pneumoniae infections, pneumonia and bloodstream infections were related to high mortality risks, while urinary tract infections showed no excess mortality (21).…”
Section: Discussionmentioning
confidence: 99%
“…Carbapenems are increasingly used for treating severe infections caused by ESBL producers. This is particularly worrisome in a scenario in which carbapenem-resistant Enterobacteriaceae (CRE) are spreading rapidly and are adversely compromising patients' outcomes (7)(8)(9)(10)(11)(12). While recent investigations have suggested that ␤-lactam/␤-lactamase inhibitors (BLBLIs) may be reliable options for the treatment of BSI due to ESBL-producing Gram-negative bacilli (ESBL-GNB), especially in nonimmunocompromised patients (13)(14)(15)(16)(17)(18)(19), other studies have found contrasting data (20,21).…”
mentioning
confidence: 99%
“…Infections with these pathogens have been associated with substantial mortality and are often difficult to treat (3,4). CPE infections are frequently caused by Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae in the United States and are associated with the spread of K. pneumoniae sequence type 258 (ST258) (5,6).…”
mentioning
confidence: 99%